Using Rubik’s Cube and a Modified LSB for Audio Steganography - Saleh, Kaziwa; Muhammad, Mihran; Ahmed, Khanda (Sulaimani Journal for Pure and Applied Sciences, 2015)
Nowadays steganography plays an important role in information security. There are various techniques to apply steganography; one such technique is Least Significant Bit (LSB). Due to consecutive embedding of data, LSB is highly vulnerable to data retrieval and manipulation. This study proposes a mixture between Rubik’s cube principle to scramble the audio data, and a modified LSB technique to hide the secret data. The modified LSB technique includes embedding using only irredundant bits of binary representation of each character in the secret message, and hiding in the lowest sample between two consecutive samples of the cover audio. The used technique makes the retrieval of secret message harder because it adds two levels of protection (scrambling, and hiding in the lowest sample) against the attempts of obtaining data; and makes the embedded data imperceptible.
Keywords: Audio Steganography LSB; Rubiks Cube